Changes in anthropometric traits and body composition over a four-year period in elite female judoka athletes - Smaruj, M.; Orkwiszewska, A.; Adam, M.; Jezyk, D.; Kostrzewa, M.; Laskowski, R. (Journal of Human Kinetics, 2019)
The aim of the study was to determine changes in the structure and composition of the body in elite female athletes over a four-year period. The study involved 12 female judo athletes with 34 somatic variables evaluated. Anthropometric evaluation was performed twice, first, when the athletes were members of the national junior team (aged 16.64 ± 1.26 years), and second, after four years, when they were members of the national senior team (aged 20.78 ± 1.27 years). The measurements were taken in accordance with the recommendations of the IBP (International Biological Program) with a set of anthropometric instruments (GPM Swiss) while following the Martin-Saller technique. The average body mass, height, BMI, fat free mass (in kg) and body fat content significantly increased, while the percentage of fat free mass significantly decreased. All of the analyzed body circumferences also increased. Increases were recorded in the width of the upper limbs and they were the width of both hands and both elbows. There was also a statistically significant increase in the value of endomorphic and mesomorphic components, while the ectomorphic component value was similar. Body composition and a substantial number of somatic features of female judokas as seniors were not yet set at the junior stage. The predominant type of the body build was the endo-mesomorphic type and changes that occurred in the sample took place mainly in accordance with this tendency. Key words: judo, female, somatic features, biological development.